2021
DOI: 10.3390/pr9030411
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Poly(alkylene succinate)s: Influence of Reaction Conditions

Abstract: Application of lipases (preferentially Candida antarctica Lipase B, CALB) for melt polycondensation of aliphatic polyesters by transesterification of activated dicarboxylic acids with diols allows to displace toxic metal and metal oxide catalysts. Immobilization of the enzyme enhances the activity and the temperature range of use. The possibility to use enzyme-catalyzed polycondensation in melt is studied and compared to results of polycondensations in solution. The experiments show that CALB successfully cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…One drawback is that the enzyme has to be removed from the final polymer in order to avoid its enzymatic degradation. In fact, CALB has been used for the synthesis of both polyesters (PBS and PCL) [24][25][26][27][28][29]. Although poly(butylene succinate-coε-caprolactone) (PBSCL) copolyesters have already been synthesized using organometallic catalyst [30][31][32], an attempt to produce them using enzymes by ring opening polymerization of CL and butylene succinate cyclic oligoesters provided low molecular weight copolymers, which could restrict their properties and consequently their applications [33].…”
Section: Introductionmentioning
confidence: 99%
“…One drawback is that the enzyme has to be removed from the final polymer in order to avoid its enzymatic degradation. In fact, CALB has been used for the synthesis of both polyesters (PBS and PCL) [24][25][26][27][28][29]. Although poly(butylene succinate-coε-caprolactone) (PBSCL) copolyesters have already been synthesized using organometallic catalyst [30][31][32], an attempt to produce them using enzymes by ring opening polymerization of CL and butylene succinate cyclic oligoesters provided low molecular weight copolymers, which could restrict their properties and consequently their applications [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, the usage of dried enzymes in enzymatic polymerization of PBS is widespread; Pellis et al [75] dried N435 under vacuum for 96 h at 25 • C and stored it in a desiccator before use, while Jiang et al [79] placed CALB into a 25 mL flask and stored it in a desiccator with phosphorus pentoxide at room temperature under high vacuum for 16 h. P 2 O 5 was also used by Sugihara et al [84] for the enzyme drying under vacuum at 25 • C for 2 h. Azim et al [80] and El Fray et al [77] used N435 predried under 0.1 mmHg vacuum at 25 • C for 24 h Enzymatic polymerization's kinetics are usually slow and thus immobilization is an approach aiming at its improvement. Interestingly, the activity of polymer-immobilized CALB (N435) may depend on the enzyme storage time, as was stated very recently by Pospiech et al [81]. The researchers used lipase CALB for melt polycondensation of aliphatic polyesters including PBS and observed that the enzymatic activity of immobilized CALB, which influenced the molar mass of the obtained products, was affected by the storage time.…”
Section: Type and Characteristics Of The Used Enzyme For Pbs Enzymatic Polymerizationmentioning
confidence: 78%
“…The overall effect of the other variables was also significant [ 86 ]. Various parameters (type of lipases, temperature, pH, stirring type and rate and monomer carbon chain length) of the polycondensation in an oil-in-water (o/w) miniemulsion (>80% in water) were evaluated when enzymatic polycondensation of dicarboxylic acids and dialcohols in aqueous polymerization media using free and immobilized lipases was developed [ 87 , 88 ].…”
Section: Biocatalysis Engineeringmentioning
confidence: 99%